Ephemeral marketing trends as a digital marketing strategy: Analyzing FOMO, gratification and user engagement in driving purchase intention - Mavilinda, Hera Febria; Rosa, Aslamia Rosa; Putri, Yulia Hamdaini (Diponegoro International Journal of Business, 2024)
The purpose of this study is to explore and analyze the influence of ephemeral marketing content in motivating users through Fear of Missing Out (FOMO) behaviors and its impact on user engagement and purchase intentionamong millennials on social media platforms, adopting the uses and gratifications theory (U&G). Furthermore, the mediating impact of gratification between Fomo and user engagement was also tested. The study utilized primary data collected via online questionnaires distributed to 200 respondents who are active users of instagram. The method employed is quantitative, with PLS-SEM data analysis technique. The results indicate that ephemeral marketing content significantly affects FOMO and customer engagement. Moreover, FOMO impacts customer engagement directly and indirectly through user satisfaction as a mediating variable. The findings also reveal that customer engagement significantly influences purchase intention. Based on these findings, it is recommended that business practitioners and marketers create and enhance digital marketing strategies through appealing ephemeral marketing content to boost consumer engagement with a brand or product, which can subsequently influence their purchasing interest.